PENGARUH PENGGUNAAN MEDIA MINI BOOK DAN CROSSWORD PUZZLE PADA MATERI KERAGAMAN DI INDONESIA TERHADAP PEMAHAMAN KONSEP - Irawan, Aisyah; Yaumi, Muhammad; Usman; Suharti (AULADUNA: Jurnal Pendidikan Dasar Islam, 2022)
Abstract This study aimed to describe the understanding of the learning concepts of students taught using the mini book and crossword puzzle media in learning material of diversity in Indonesia. The type of research was a quasi-experimental design using a pretest-posttest non-equivalent control group design. The population 3 classes, namely class IV A, B, and C of MIN Bima City for the 2020/2021 academic year, consisting of 97 students. The instrument used was a test. The data analysis technique used descriptive and inferential statistics. The results indicated that (1) the average value of students’ understanding taught with mini-book was higher than without using media, (2) students taught with crossword puzzle media were higher than without using media, and (3) there was a significant difference in students’ understanding of learning concepts on the material of diversity in Indonesia between the mini book and crossword puzzle media. The implication of this research showed that the mini book and crossword puzzle media could increase students’ understanding of learning concepts.